Enhanced Fractionation of Guava Seed Cake Using Alkali-Catalyzed Ethanol Organosolv Pretreatment - Zamora Zamora, Hernán Darío [UNESP]; de Freitas, Caroline [UNESP]; Pasquini, Daniel; Masarin, Fernando [UNESP]; Brienzo, Michel [UNESP] (Springer Nature, 2025)
This study presents the performance of NaOH-catalized ethanolic organosolv pretreatment on guava seed cake (waste industrially generated after oil extraction process of guava seed) aiming to extract hemicellulose and lignin. The pretreatment assessment also included cellulose conversion to glucose by enzymatic hydrolysis. The pretreatment used NaOH 10 and 60% (m/m), temperatures of 120 and 170 °C, and ethanolic aqueous solution concentrations of 30 and 70%. NaOH concentration was the most significant factor in the extraction yield of hemicelluloses, and the temperature was the most significant in the lignin extraction and cellulose conversion to glucose. At 170 °C, ethanolic aqueous solution concentration of 30%, and NaOH concentration of 60%, the highest yield of extracted hemicellulose was 97.3%. The maximum extraction of lignin (45%) was reached at 170 °C, ethanol aqueous solution concentration of 70%, and NaOH concentration of 60%. The best cellulose conversion to glucose (50.3%) was obtained with material pretreated at 170 °C, ethanol aqueous solution concentration of 30%, and NaOH concentration of 60%. The extracted hemicelluloses presented low molecular weight (14.7–59.3 kDa), and, according to qualitative chemical analysis, the extracted hemicelluloses and lignin showed great correspondence with the commercial ones.
Keywords: Biorefinery; Enzymatic hydrolysis; Fruit waste; Hemicellulose; Lignin